2022
DOI: 10.3390/ijerph191912373
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Remote Working on Employees’ Performance and Well-Being: An Evidence-Based Systematic Review

Abstract: Remote working refers to a working model in which employees can pursue work tasks outside the organization due to the use of technology. Several research papers showed that different assumptions are linked to remote work because of the flexibility and autonomy granted to employees when working remotely or from home. This review consistently aims to describe remote work’s role in employees’ well-being and performance. Using the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…It has been repeatedly argued that an advantage of WFH is allowing a better balance between a person's job and their personal and family life (Baruch 2001). This variable has been widely proven to be significant in explaining work satisfaction (Ferrara et al 2022). However, weak (or nonexistent) boundaries between household and work regarding time spent and space used in the home may blur limits between work and personal environments, and then, a conflict between job and home may arise (Baruch 2001;Harris 2003;Beckel and Fisher 2022;Kohont and Ignjatović 2022).…”
Section: Perceptions Of the Personal Benefits Of Working From Homementioning
confidence: 99%
See 3 more Smart Citations
“…It has been repeatedly argued that an advantage of WFH is allowing a better balance between a person's job and their personal and family life (Baruch 2001). This variable has been widely proven to be significant in explaining work satisfaction (Ferrara et al 2022). However, weak (or nonexistent) boundaries between household and work regarding time spent and space used in the home may blur limits between work and personal environments, and then, a conflict between job and home may arise (Baruch 2001;Harris 2003;Beckel and Fisher 2022;Kohont and Ignjatović 2022).…”
Section: Perceptions Of the Personal Benefits Of Working From Homementioning
confidence: 99%
“…CIS (2021) reports that 95% of employees financed connectivity and 65% used their own electronic devices to carry out work from home during the COVID-19 pandemic. Likewise, organizational support implies not using traditional instruments to evaluate workers' contributions; instead of using presentism criteria, they should use objectives (Baruch 2001) that are based on trust and measurable items (Beauregard et al 2019) and should align organizational values with employee values (Ferrara et al 2022). Otherwise, WFH can be perceived as inhibiting being professionally promoted.…”
Section: Organizational Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported positive and negative outcomes of WFH in different home working arrangements and home conditions [ 15 , 16 , 17 , 18 ]. On the positive side, at the personal level, studies reported lower time pressure [ 19 ], better control of work schedules [ 17 ], higher work motivation [ 20 ], higher life satisfaction [ 21 ], and less work-family conflict [ 19 ].…”
Section: Introductionmentioning
confidence: 99%